GREEN MARKETING STRATEGY: DO CONTENT MARKETING, BRAND PURPOSE, AND E-WOM AFFECT CONSUMER PURCHASE INTENTION? - Sriayudha, Yayuk; Octavia, Ade; Heriberta, Heriberta; Roza, Suswita (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
Marketing strategies for environmentally friendly products focus on creating and promoting products that are responsible toward both the environment and society, while building a loyal customer base that supports the commitment to environmental preservation. As digital technology continues to develop, consumers increasingly seek product information online, read reviews, and engage in discussions on digital platforms before making purchasing decisions. Combining engaging content marketing, emphasizing a meaningful brand purpose, and leveraging the power of e-WOM is predicted to create a significant impact on consumers’ purchase intention toward green products.The objectives of this study are to analyze: (1) the influence of content marketing and brand purpose on e-WOM, (2) the influence of content marketing and brand purpose on purchase intention for green products, (3) the influence of e-WOM on purchase intention for green products, and (4) the influence of content marketing and brand purpose on purchase intention for green products mediated by e-WOM. The research method is descriptive quantitative research using a sample survey. The population consists of green product consumers, with a total sample of 100 respondents. The analysis uses SEM with the PLS3 analytical tool.The results of the study show that content marketing and brand purpose have a significant influence on e-WOM and purchase intention for environmentally products. This research carries urgency considering the importance of providing comprehensive understanding to consumers as agents of change through approaches such as content marketing, brand purpose, and e-WOM in shaping purchase intention, particularly in the context of environmentally friendly products.